Respuesta :

Hello!

First you find the least common multiplier which is 2x(x + 2)

[tex] \frac{1}{x} * 2x(x + 2) + \frac{1}{x + 2} * 2x(x + 2) = \frac{1}{2} * 2x(x + 2)[/tex]

Simplify

2(x + 2) + 2x = x(x + 2)

Now you solve it algebraically

Distribute the 2

2x + 4 + 2x = x(x + 2)

Distribute the x

[tex]2x + 4 + 2x = x^{2} +2x[/tex]

Combine like terms

[tex]4x + 4 = x^{2} +2x[/tex]

Subtract 4 from both sides

[tex] x^{2} + 2x - 4 = 4x[/tex]

Subtract 4x from both sides

[tex] x^{2} - 2x - 4 = 0[/tex]

Now you put this into the quadratic formula

[tex]x = \frac{-(-2) + and - \sqrt{(-2)^{2}- 4 * 1 * (-4) } }{2 * 1} [/tex]

Simplify

[tex]x = \frac{2 + and - \sqrt{20} }{2} [/tex]

Factor the sqrt of 20

[tex]x = \frac{2 + and -2 \sqrt{5} }{2} [/tex]

Factor 2 + and - the 2 * sqrt of 5

[tex] \frac{2(1 + and - \sqrt{5}) }{2} [/tex]

The 2's cancel each other other

[tex]x = 1 + and - \sqrt{5} [/tex]

The answers are [tex]x = 1 + \sqrt{5} and x = 1- \sqrt{5} [/tex]

Hope this helps!